THE GROWTH OF WHITE CORN PLANT WITH SEVERAL PHOSPOR FERTILIZERS AND MYCORRHIZA APPLICATION IN INCEPTISOL AT LUMBAN LOBU VILLAGE, BONATUA LUNASI SUBDISTRICT TOBA SAMOSIR DISTRICT- SUMATERA UTARA - Andrew Hans Prima; Bintang Bintang; Hardy Guchi; Benny Hidayat (Badan Penerbitan Fakultas Pertanian (BPFP), 2018)
The criteria of P available on Inceptisol soil are low, so P fertilizer and mycorrhiza application is needed to increase P available on the soil. This research aim was to determine the growth of white corn plants by various P fertilizers and mycorrhiza application in Inceptisol soil at Lumban Lobu Village, Bonatua Lunasi Subdistrict, Toba Samosir District Sumatera Utara. The method used was Factorial Randomized Block Design with two factors and two repetitions. The first factor is the source of P consists of 7 treatments: P0 (control); P1 (TSP fertilizer); P2 (phosphate rock fertilizer); P3 (chicken manure); P4 (cow manure); P5 (guano fertilizer) and P6 (rice husk biochar) and the second factor is mycorrhiza with two treatments: M0 (0 g / plot) and M1 (30g / plot). Parameters observed were plant height, organic C content, soil H2O pH and degree of mycorrhiza infection. The research results showed that the application of P sources did not significantly increase the growth of white corn plants. The application of mycorrhiza significantly increased the degree of root infection and the interaction of P sources and mycorrhiza significantly increased the degree of root infection.Keywords : P Sources, Mycorrhiza, Inceptisol, White Corn.